Process Optimization of Biomimetic Calcium Phosphate Coating on 3D Printed Porous Polyethylene by Using Statistical Design of Experiment - Faungchat Thammarakcharoen (Science Faculty of Chiang Mai University, 2019)
Porous polyethylene has been widely used as implant for both hard and soft tissue replacement since it allowed tissue ingrowth and vascularization within its pores. However, due to its inertness, several studies attempted to improve its bioactivity through surface modification or coating. Biomimetic process which mimics the biological process in nature has been shown to be able to produce bioactive calcium phosphate layer on the surface of biomaterials at low temperature. This process was; thus, applied to create a calcium coating on three dimensionally printed porous polyethylene to possibly increase its bioactivity. Statistical design of experimental methodology based on Taguchi L36 design was used to study the effect of various processing parameters on the amount of calcium phosphate coating produced by such technique. The coating process was divided into three main steps and eleven control factors were studied including pretreatment step (pressure, sodium hydroxide concentration, temperature and time), seeding step (pressure, drying method and number of repetition) and coating step (time, temperature, surface to volume ratio and pressure). It was found that pretreatment pressure were the dominant factors with the greatest contribution while pretreatment temperature, seeding pressure, number of seeding repetition, coating time and coating temperature were significant factors. Other control factors had negligible effects on the coating content. For all conditions, plate-like calcium phosphate crystals were similarly found to grow on the surface of 3D printed porous polyethylene, but the crystal size varied. X-ray diffraction revealed that all the coatings consisted of octacalcium phosphate (OCP) and hydroxyapatite (HA) as main phases.